DASAR TARI SULSEL PADA MAHASISWA PRODI PENDIDIKAN SENI DRAMA, TARI, DAN MUSIK FSD UNM SEBAGAI ALIH BUDAYA ETNIS SULAWESI SELATAN - Padalia, Andi; Saputra, Andi Taslim; Salawati, Bau (Universitas Negeri Makassar, 2024)
South Sulawesi Dance Basics as a subject for Drama, Dance, and Music Education Students is one of the educational means to develop positive aesthetic experiences for students in achieving basic arts educator skills. This research was conducted to ensure that cultural transfer is depicted in the process of learning the basics of South Sulawesi dance, because this is an important indicator of South Sulawesi ethnic cultural transfer that is instructive. The aim of this research is to find out: a) how the learning of the basics of South Sulawesi dance is transmitted to students of the UNM FSD Dramatic Arts, Dance, and Music education study program; and b) how the transfer of ethnic culture from South Sulawesi is depicted in the educational learning of the basics of South Sulawesi dance. This research uses a qualitative method with a case study approach as the research design. This research uses the theory of the process of transfer (by educators) and acceptance (by students) related to cultural substances, in this case learning the basics of South Sulawesi dance. The method used uses observation, interviews, and data analysis. The research findings show that: 1) the description of the learning process and learning outcomes and specific parts, such as various basic movements of South Sulawesi dance; and 2) the basis of South Sulawesi dance in learning functions as a transfer of South Sulawesi ethnic culture.